Reduction in the use of fossil fuels by improving the interconnection power system oscillation - Mohammed Tsebia; Hamid Bentarzi (Institute of Advanced Engineering and Science, 2023)
Many international organizations have called for reducing usage of renewable energy as a means to reduce carbon dioxide emissions, this paper studies the case of electricity production based to fossil fuels. Currently existing solutions is to shift from fossil fuels to clean renewable energy. Electrical interconnections are used between large-scale areas; these interconnections have a major problem that is the phenomenon of oscillations. The amount of fossil energy used by power plants depends on the electrical load required. with these conditions it is not possible to reduce the amount of energy required to satisfy the electrical load required. The solution proposed in this paper is the improvement of interarea oscillation using phasor measurement unit technology for real-time monitoring and accuracy of measurements. We tested the proposed solution for the north African power system. The results show the importance of improving interconnection networks to reduce fossil fuels use.